Analysis and simulation of reactive power theory for harmonic elimination using shunt active power filter. (17th February 2021) - Chawla, Pankaj; Lalwani, Mahendra
A distinct type of load draws non-sinusoidal current from the main supply, which cause harmonic disturbance and reduce the power quality. The major cause of harmonic distortion is this nonlinear load in a power system. In addition, the nonlinear loads causing harmonic distortion can interrelate harmfully with power system equipment, mainly motors, capacitors and transformers causing extra losses. In order to minimise these extra loses due to harmonic disturbance; the shunt active power filters (SAPFs) is investigated to maximize power quality. This paper presents the control method for extracting the reference currents for SAPF using instantaneous reactive power theory (IRPT). It has been evaluated and their performance is brought to a comparison under distorted supply and nonlinear load circumstances. This new speculation gives a general description of IRPT that is applicable for balanced or unbalanced loads and sinusoidal or non-sinusoidal waveforms in three-phase power systems compensation or non-compensation zero-sequence currents and voltages.